Gestión de riesgos laborales y seguridad del paciente en entornos hospitalarios de la ciudad de Ibagué (2022)
The health agent – patient relationship generates bidirectional risks for patients and workers of health service institutes (or its Spanish initials IPS). Particularly, biosecurity failures and attention protocols breaches generate risks that are analyzed and controlled in different ways in the public health system. In that context, this study looked for the relation between occupational risk preventive programs and patient safety actions in the nursing practice of heath institutions in the city of Ibagué. The results were obtained by using a questionnaire based on the National Poll of Occupational Health and Safety Conditions of 2013. As a conclusion, infrastructure deficiencies, work overload and unknowledge about prevention actions cause a decreasing on the quality of the patient service in IPS and an increasing of the risk of adverse events that affect workers health. This research showed the importance of integrated planning of security patient actions and occupational risk prevention, with the purpose of generate healthy environments for workers and patients.